Protection against neutrophil extracellular trap (NET) toxicity by antioxidant monoHER - Astuti, Puji; Beurskens, Danielle M A; Vajen, Tanja; Nicolaes, Gerry A F; Zhang, Ming; Haenen, Guido R M M (UI Scholars Hub, 2019)
Background: Neutrophil extracellular traps (NET) are extracellular fibers produced by activated neutrophils to kill bacteria. NET was recently found to be associated with several diseases, such as autoimmune diseases. NET formation, called NETosis, is reactive oxygen species (ROS) dependent, thereby, prompting us to study its inhibition by potent antioxidant monoHER as well as to study monoHER protection against NET toxicity caused by NET constituent histone 3 on endothelial cells. Methods: Freshly isolated neutrophils from male donors were stimulated with PMA to induce NET formation. The effect of monoHER (50 µM) on oxidative burst (O2●− production) and NET formation was determined by fluorescence microscopy. Flow cytometry was used to determine the protective effect of monoHER against NET toxicity constituent histone 3 in EA.hy926 cells. Data was evaluated using ANOVA followed by the Bonferroni post-hoc test. Results: MonoHER significantly reduced (p < 0.01) O2●− production of PMA-stimulated neutrophils and consequently inhibited NET formation. MonoHER could also counteract histone 3 toxicity in EA.hy926 cells. Conclusions: MonoHER might inhibit ROS-dependent NETosis pathway and also protect the endothelial cells against NET toxicity.